Cyber Risk Awareness of German SMEs: An Empirical Study on the Influence of Biases and Heuristics - Salzberger, Alina (Zeitschrift für die gesamte Versicherungswissenschaft, 2024)
The number of successful cyberattacks against small and medium-sized enterprises (SMEs) is increasing steadily, while various studies already showed that especially SMEs often lack an appropriate awareness concerning their own cyber risk exposure. There-fore, the aim of this paper is to analyze the cyber risk perception of German SMEs and investigate the influence of biases and heuristics on German SMEs’ cyber risk awareness. This is done based on a questionnaire survey among 1,540 owners and managers of German SMEs with up to 250 employees. The results show that perceived probabilities for cyberattacks against the own enterprise are significantly lower rated than for comparable organizations, which indicates the influence of an optimistic bias with respect to risk es-timates. Additionally, perceived cyber risk also varies significantly depending on direct and indirect experience as well as the stated degree of confidence in one’s own cyber risk management capabilities, indicating the presence of the availability heuristic and the overconfidence bias in cyber risk perceptions.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Behavioral Influences; Biases; cyber risk awareness; Cyber risk perception; Heuristics; SMEs